Avaliação dos índices plaquetários, atividade da e-ntpdase e da ecto-5'-nucleotidase em plaquetas de gestantes normotensas e com pré-eclâmpsia - Almeida, Taís Corrêa (2018)
Preeclampsia is the most common medical complication in pregnancy, accounting for the main cause of maternal and perinatal mortality and morbidity. Its etiology remains unknown which makes primary prevention difficult. It is a fact that gestation has a hemostatic imbalance with a tendency to hypercoagulability and an increased risk of thrombosis. These changes involve the purinergic signaling, which is composed of nucleotides and nucleosides, their respective receptors, and enzymes responsible for their degradation. During the inflammatory process, ATP, ADP, AMP and adenosine, which correlate directly with the activity of E-NTPDase, E-5'-nucleotidase, E- NPP and E-ADA. Adenine nucleotides may interact with purinergic receptors on the cell surface. The effects of extracellular ATP are controlled by the ectonucleotidases E-NTPDase and Ecto-5'-nucleotidase, which act on ATP and its degradation products, reducing its concentration in the medium and culminating in the production of adenosine, which acts as an immunomodulator or is converted to inosine by adenosine deaminase (E-ADA). Considering that hemostatic and inflammatory changes associated with normal pregnancy are more exacerbated in PE, it becomes relevant to study these mechanisms as a way of understanding the profile of this imbalance and act preventively. Therefore, the analysis of platelet parameters, as well as activity and expression of E-NTPDase and Ecto-5'nucleotidase were performed in 150 women divided into three groups: non-pregnant (n = 50), normotensive pregnant women (n = 50) and pregnant women with PE (n = 50). The results showed an increase of 74 (P < 0.001) and 72% (P < 0.01) in platelet aggregation in the addition of 5 μM and 10 μM, respectively, of adenosine diphosphate agonist (ADP); reduction of 19% (P < 0.05) of platelet count; 39% (P < 0.05) increase in immature platelet fraction (IPF); 7-fold increase (P < 0.001) in the E-ADA activity; reduction of 37 (P < 0.001) and 36% (P < 0.05) in the hydrolysis of ATP and ADP, respectively, and a correlation between platelet count, IPF, E-NTPDase and Ecto-5-'nucleotidase activity and expression in pregnant women with PE. Together, these results suggest that the endothelial dysfunction present in pregnant women with PE exacerbates the inflammatory and platelet aggregation mechanisms. The organism reacts to this inflammatory microenvironment through the reduced hydrolysis of ATP, with consequent platelet inhibition. However, this mechanism does not seem to be sufficient to overcome the disease since the disease is maintained. Therefore, the process of platelet aggregation as well as purinergic signaling seems to play an important role in the immune and inflammatory responses contributing to the clinical evolution of PE. Consequently, the evaluation of these parameters can lead to the development of protocols to prevent or treat this pathology effectively.